Military terms in the book of Boburnama - Tursunaliyeva Durdona (Journal of Learning on History and Social Sciences, 2024)
This article describes the military terms in Zahiriddin Muhammad Babur's work "Baburnoma", as well as Babur's creative ideas and how important they are for the young generation